Applying an intersectional lens to scaling - Ewell, Hanna; Huyer, Sophia; Gondwe, Therese (2025)
As climate change disproportionately affects smallholder farmers, especially women and marginalized groups, integrating intersectionality into agricultural research for development (AR4D) is essential for inclusive and equitable scaling. Intersectional analysis reveals how overlapping identities (e.g., gender, age, ethnicity, disability, socioeconomic status) create compounded disadvantages often overlooked in innovation processes. The AICCRA project demonstrates how tailoring climate-smart agriculture (CSA) and climate information services (CIS) to diverse social realities, through participatory design, targeted training, and local governance—can advance empowerment and social equity.